2018
DOI: 10.1002/pros.23696
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between PSA kinetics and Tc‐99m HYNIC PSMA SPECT/CT detection rates of biochemical recurrence in patients with prostate cancer after radical prostatectomy

Abstract: The Tc-99m HYNIC PSMA SPECT/CT detection rate is influenced by trigger PSA, PSAdt, and PSAvel. Like PSA, PSAdt is an independent predictor of Tc-99m HYNIC PSMA SPECT/CT. PSAdt should be taken into account by physicians especially when PSA <1 ng/mL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 27 publications
1
5
0
2
Order By: Relevance
“…In a large study of 225 patients reported by Schmidkonz et al [15], it was found that the detection capabilities of prostate cancer with the biochemical progression of [ 99m Tc]Tc-MIP-1404 SPECT-CT are comparable to those of 68 Ga-PSMA PET-CT at levels of PSA > 2 ng/mL. At lower than these values and a smaller volume of the tumour tissue substrate, the sensitivity of SPECT-CT studies is reduced to 54% [16]. Liu et al [17], report that at lower PSA values < 0.5 ng/mL the diagnostic value of [ 99m Tc]HYNIC-PSMA SPECT-CT is 48.6%.…”
Section: Discussionmentioning
confidence: 95%
“…In a large study of 225 patients reported by Schmidkonz et al [15], it was found that the detection capabilities of prostate cancer with the biochemical progression of [ 99m Tc]Tc-MIP-1404 SPECT-CT are comparable to those of 68 Ga-PSMA PET-CT at levels of PSA > 2 ng/mL. At lower than these values and a smaller volume of the tumour tissue substrate, the sensitivity of SPECT-CT studies is reduced to 54% [16]. Liu et al [17], report that at lower PSA values < 0.5 ng/mL the diagnostic value of [ 99m Tc]HYNIC-PSMA SPECT-CT is 48.6%.…”
Section: Discussionmentioning
confidence: 95%
“…Two studies by Schmidkonz and colleagues reported that the overall detection rates of 99mTc-MIP-1404 for BCR of PCa were 77% (174/225) (10) and 70% (42/60) (12), respectively. Similarly, Su et al (20) and Liu et al (21) reported detection rates of 78% (39/50) and 73% (151/208) for 99mTc-HYNIC-PSMA in the localization of BCR. A detection rate of 57% (87/152) was reported for 99mTc-PSMA-I&S, which is lower than our finding (22).…”
Section: Discussionmentioning
confidence: 76%
“…While the overall detection rate of PSMA SPECT/CT of 77% was comparable to PET diagnostics, it is important to note that for low PSA levels (<2 ng/mL), SPECT/CT showed considerably lower detection rates of only 54% compared to PSMA PET/CT. The highest detection rate for SPECT/CT at very low PSA levels (<0.5 ng/mL) was described by Liu et al [44] with 48.6%. In patients with PSA relapse and PSA values <1 ng/mL after primary treatment, two smaller retrospective studies showed detection rates for PSMA SPECT/CT of only 36.4% and 30%, respectively [4546].…”
Section: Main Bodymentioning
confidence: 99%